Social dialecticisms: the structure of lexical and semantic field of «Man» (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
The article deals with the structural-semantic features of lexical units that mark the names of man. Attention is focused on historical and etymological basis of individual social dialecticisms. Materials used modern Ukrainian artistic texts.
Keywords: lexical and semantic field; lexical and semantic group; lexical and semantic subgroup; social dialecticism